RANCANGAN PENGELOLAAN JURNAL ONLINE MAHASISWA MENGGUNAKAN OPEN JOURNAL SYSTEM (Studi Kasus : Prodi Teknik Informatika UIKA) - Fatimah, Fety; Jaenudin, Jejen (Krea-TIF: Jurnal Teknik Informatika, 2015)
In order to develop the online journal of Informatics Engineering Department into an online-based scientific journal (e-journal) in Informatics Engineering. While this research results of the students only published without going through the process of learning, examination and editing. The purpose of the management of online journals of students in order to maintain the quality of journal research results and publications. In this study the management of student online journals (JOM) using Open Journal System (OJS). OJS is useful for managing its journals from starting online submission, reviewer process, copyediting process, proofreading process, etc. until the script can be published in OJS. All these processes are done online using OJS. The design of this JOM Management as a medium that can bridge the researchers (students) and reviewers (experts and the campus) and to publicize the field of informatics engineering so that it can be done effectively and efficiently.